Communication Amongst Village Women's Groups As A Catalyst For Social Development - Intan, Dyah Noor; Saidah, Siti; Aziz, Firman (Jurnal Scientia, 2024)
This research examines the role of communication among groups of village women as a catalyst for social development through a literature review method. Effective communication within village women's groups has great potential to improve various aspects of social development, including health, education and economic empowerment. However, challenges such as cultural barriers, infrastructure limitations, and internal conflicts can reduce the positive impact of communication. External support and strong leadership have proven important in facilitating productive communication. The research results show that good communication can increase access to basic services and strengthen participation in social programs. This research emphasizes the importance of a holistic approach to overcoming challenges and maximizing the benefits of communication in rural women's groups, as well as the need for further research to develop more effective strategies.